The study of the area of footpath between male and female elite distant runners under different running speeds of a treadmill - Wang, J. C.; Lin, M. H.; Lu, Y. H. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
The purpose of this study was to investigate and to compare the difference of area of footpath between male and female elite distant runners under 3 m/s and 4 m/s running speeds on a treadmill. There were 9 male and 7 female subjects jointed this study. AJVC DVL-9800 digital camera was utilized to record subject's running movement, and the Ariel Performance Analysis System was used for digitizing. The t-test statistics was used to test the difference between variables. The results indicated that both male and female runners' areas of footpaths were greater when the running speed was increased, and there was no significant difference between male and female runners.